Do The Tax Court Decisions Fulfill Tax Justice? Literature Review - Supriyadi, Mohammad Wangsit; Supriyadi, Supriyadi (Educoretax, 2024)
Based on MK decision Number 26/PUU-XXI/2023, the Constitutional Court (MK) has determined that the Tax Court Institution, which was formerly under the Ministry of Finance, will henceforth be under the Supreme Court (MA) no later than December 31, 2026. In accordance with Tax Court Law Number 14 of 2002, the purpose of this study is to locate and evaluate tax court rulings with the goal of enhancing tax compliance. A qualitative technique is employed in the research methodology, together with a literature review analysis of research findings and tax laws pertaining to court rulings and tax compliance. The findings demonstrate how judicial rulings support tax justice. Taxpayers have great faith in the Tax Court to settle their tax disputes. It is hoped that by consolidating the Tax Court under the Supreme Court, the Tax Court will play a larger role in resolving tax disputes and offering justice.